Place and Health as Complex Systems A Case Study and Empirical Test - Castellani, Brian; Rajaram, Rajeev; Buckwalter, J. Galen; Ball, Michael; Hafferty, Frederic (SpringerBriefs in Public Health, 2015)
The history of public health has focused on direct relationships between problems and solutions: vaccinations against diseases, ad campaigns targeting risky behaviors. But the accelerating pace and mounting intricacies of our lives are challenging the field to find new scientific methods for studying community health. The complexities of place (COP) approach is emerging as one such promising method.   Place and Health as Complex Systems demonstrates how COP works, making an empirical case for its use in for designing and implementing interventions. This brief resource reviews the defining characteristics of places as dynamic and evolving social systems, rigorously testing them as well as the COP approach itself. The study, of twenty communities within one county in the Midwest, combines case-based methods and complexity science to determine whether COP improves upon traditional statistical methods of public health research. Its conclusions reveal strengths and limitations of the approach, immediate possibilities for its use, and challenges regarding future research. Included in the coverage:   Characteristics of places and the complexities of place approach. The Definitional Test of Complex Systems. Case-based modeling using the SACS toolkit. Methods, maps, and measures used in the study. Places as nodes within larger networks. Places as power-based conflicted negotiations.   Place and Health as Complex Systems brings COP into greater prominence in public health research, and is also valuable to researchers in related fields such as demography, health geography, community health, urban planning, and epidemiology.  .